Evaluation of the Impact of Stunting Policy in Improving Nutrition in Banyumas Regency - Amud Sunarya; Milwan; Jayanti Armida Sari (Ilomata International Journal of Social Science, 2026)
This study examines the effectiveness of Banyumas Regent Regulation Number 25 of 2020 in reducing stunting prevalence in Banyumas Regency, where stunting remains a critical public health and development issue. The research question is: How effective is the regulation in reducing stunting prevalence through targeted nutritional interventions. A mixed-methods approach was employed, combining quantitative survey data from families with toddlers and qualitative interviews with key stakeholders to assess policy implementation and outcomes. The findings show a significant decline in stunting prevalence in 2022 following the regulation’s implementation, although an increase in 2023 indicates sustainability challenges. Unlike national-level policy frameworks that provide broad strategic guidelines and standardized targets across regions, this regional regulation translates national priorities into context-specific interventions tailored to local demographic, socio-economic, and institutional conditions in Banyumas. Compared to other local case studies that often focus on program-level initiatives or pilot projects, this regulation represents a formalized and binding district-level legal instrument that integrates cross-sector coordination, budget allocation, and monitoring mechanisms within the local governance structure. The study concludes that while the regulation demonstrated initial effectiveness, sustained stunting reduction requires stronger program implementation, cross-sector coordination, and continuous policy support to ensure long-term impact at the regional level.